Pengaruh Kadar Thiamine (Vitamin B1) terhadap Lebar Tudung Jamur Tiram Putih (Pleurotus ostreatus) dan Sumbangsihnya pada Materi Ciri dan Peran Jamur di Kelas X MA/SMA - Siti Jariah; Munir Abdul Mungin; Fitratul Aini (BIO-SITE |Biologi dan Sains Terapan, 2016)
Indonesia is one of the centers of biodiversity in particular areas of food, which one of them is from a species of white oyster mushroom (Pleurotus ostreatus). To improve the effectiveness and efficiency of production time associated with fulfilling the request of the oyster mushroom (Pleurotus ostreatus) is high in the market, the utilization of thiamine (vitamin B1) need to be investigated. This study aims to determine the levels of thiamine (vitamin B1), which is best used in the growth of oyster mushroom (Pleurotus ostreatus). As for the levels of thiamine (vitamin B1) used in this study use the unit ppm (parts per million), namely: B0 (control / without giving thiamine), B1 (thiamine with levels of 0.1 ppm), B2 (thiamine grading 0.2 ppm), B3 (thiamine with levels of 0.3 ppm). Parameters measured were the growth of oyster mushroom (Pleurotus ostreatus) is wide hood (cm). This study used quantitative experiments and research design complete randomized design with four treatments and six times as many repetitions as well as research along with the observations made on 21 June to 11 July 2015 (in 20 days) in the House of White Oyster Mushroom Production Nurseries, Ogan Komering Ulu Timur (OKUT). Administration of thiamine (vitamin B1) performed 2 days and watering is done every day, morning and evening using a sprayer. Low temperatures and high humidity is maintained by using hygrothermometer. Conclusions from the study and based on data analysis (ANOVA / Analysis of Variance) and F test showed that administration of thiamine (vitamin B1) does not provide an effective influence on the growth of oyster mushroom (Pleurotus ostreatus). Information thiamine (vitamin B1), which serves for the growth of oyster mushroom (Pleurotus ostreatus) is expected to be beneficial to its development as a commercial commodity mushrooms.